Navigating The Algorithm: AI Opportunities and Challenges in Medical English - Jumaida Fajar Nassriati (STMIK Indonesia Banda Aceh, 2025)
This study employed a qualitative descriptive design to explore the opportunities and challenges perceived by health students at STIKES Darussalam Lhokseumawe in utilizing AI for English language learning. Data were collected through semi-structured interviews with 18 purposively selected students from the nursing program and analyzed using a thematic analysis approach. The findings revealed three overarching themes. First, students recognized AI as a powerful facilitator of personalized learning, providing on-demand, context-specific practice in medical English through chatbots and writing tools. Second, they navigated significant challenges, including anxiety over AI hallucinations and concerns about superficial learning and skill atrophy. Third, a crucial institutional guidance vacuum was identified, where the absence of formal policies or pedagogical support amplified these challenges and created ethical ambiguities. The study concludes that while students are proactively and resourcefully leveraging AI, the full potential of these tools is hindered without institutional scaffolding. This research underscores the urgent need for pedagogical integration, clear ethical guidelines, and faculty development to transform AI from a precarious, student-driven tool into an effectively supported educational resource